A PVA periosteum material for bone tissue regeneration and its preparation method and application

By adopting bilayer structure and crosslinking technology in periosteal materials, the problem of uneven mechanical properties after degradation of periosteal materials is solved, and the periosteal can still provide stable mechanical support and structural stability after degradation, and promote the repair of bone tissue. and regeneration.

CN118807000BActive Publication Date: 2024-12-24XIANGFU LABORATORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297748.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing periosteal materials have uneven mechanical properties after degradation, which are difficult to resist the invasion of soft tissues and blood vessels, and cannot effectively provide mechanical support and structural stability, affecting the repair of bone tissue.

Method used

Using a bilayer structure PVA periosteal material, the inner layer is made of 2-hydroxypropyl trimethylammonium chloride chitosan and polyvinyl alcohol as the matrix, and the outer layer is made of polyp-dioxane, polyethyleneimine and oligosil Sugar is composed of and cross-linked by glutaraldehyde to form chemical and physical cross-linking structures, ensuring tight connection between the inner and outer layers, improving mechanical properties and biocompatibility.

Benefits of technology

The uniformity of the mechanical properties of periosteal materials after degradation is achieved, it can effectively resist the invasion of soft tissues and blood vessels, provide stable mechanical support, promote the repair and regeneration of bone tissue, and improve the patient's rehabilitation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a PVA periosteal material for bone tissue regeneration and its preparation method and application, which belongs to the technical field of medical periosteal materials. The periosteal material includes an inner layer and an outer layer, and glutaraldehyde is coated between the inner layer and the outer layer; the inner layer is in contact with human bone repair material, and the inner layer is a nanofiber layer formed by using 2-hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol as a matrix and bioceramic particles as additives; the outer layer is a nanofiber layer formed by using polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate. The periosteal material is improved on the basis of the existing double-layer structure periosteum. Even if the periosteal material is degraded in the later stage, the inner layer and the outer layer of the undegraded part will still be tightly connected, and the invasion of soft tissue and blood vessels can still be resisted in the later stage, providing sufficient mechanical support and maintaining structural stability for the repair of later bone tissue, thereby improving the patient's rehabilitation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a PVA periosteal material for bone tissue regeneration and a preparation method and application thereof, belonging to the technical field of medical periosteal materials. Background Art

[0002] Currently, due to trauma, blast injury, diseases such as osteomyelitis, osteonecrosis or osteosarcoma, or surgical resection, bone tissue is lost or cavitated, and it is necessary to replace bone tissue or promote its regeneration. Due to the matrix characteristics of bone tissue itself and the lack of blood and lymph flow during the regeneration process, bone regeneration and repair are limited. The most common methods are to use autologous vascularized bone grafts (autografts), allogeneic transplants (usually from corpses), or resorbable or non-resorbable "artificial bones" for bone replacement. At present, autologous bone transplantation has good clinical effects and a high success rate. Studies have shown that autologous bone is the main reason for achieving bone defect repair because it has a complete periosteum.

[0003] Periosteum is an important component of normal bone tissue. It is a thin, tough, and dense connective tissue membrane that wraps around bone tissue. In current bone repair treatments, people tend to focus on the bone defect itself and ignore the role of the periosteum. The periosteum can play the following roles in the repair of bone defects:

[0004] 1. Resist the invasion of soft tissue and blood vessels, provide growth factors to the defect site and recruit osteoblasts to accelerate the regeneration of bone tissue;

[0005] 2. Provide sufficient mechanical support for the repair of bone tissue and maintain structural stability.

[0006] At present, the research focus on artificial periosteum materials is on biological periosteum materials, hydrogel composite growth factor periosteum materials, etc. Among them, PVA is often used as the main component of periosteum to guide bone tissue regeneration due to its good biocompatibility, but there are problems such as mismatch between degradation rate and osteogenesis rate and poor mechanical properties. There are currently two ways to solve this problem. One is to use bioceramic materials, two-dimensional nanomaterials and polyvinyl alcohol to prepare composite materials for improvement. However, the composite periosteum prepared from the above materials still has the problems of poor dispersion of ceramic materials or nanomaterials, displacement of ceramic materials or nanomaterials during degradation, and uneven degradation of matrix materials. The above situation will lead to uneven distribution of mechanical properties of the periosteum, and even if the initial mechanical distribution of the periosteum is uniform, the mechanical properties will become uneven again after degradation in the later stage. The second is to prepare a double-layer structure periosteum, and prepare a periosteum for a specific disease by combining an inner layer and an outer layer, such as the double-layer structure periosteum for diabetic bone repair disclosed in patent CN111265722A. The periosteum can help improve the supporting effect of the periosteum, facilitate osteoblast attachment and growth, and block the growth of other soft tissues. However, this type of double-layer structure periosteum will partially separate with the degradation of the inner and outer layers, which will also lead to the problem of uneven mechanical properties after degradation in the later stage.

[0007] Therefore, both of the above-mentioned two improvement methods will have the problem of uneven mechanical properties in the later stage of degradation. This problem will make it difficult for the periosteum to resist the invasion of soft tissue and blood vessels in the later stage, and it will be difficult to provide sufficient mechanical support and maintain structural stability for the repair of bone tissue in the later stage, thus failing to truly and effectively simulate the function of the human periosteum. Summary of the invention

[0008] In order to solve the above problems, a PVA periosteal material for bone tissue regeneration and a preparation method and application thereof are provided. The periosteal material is improved on the basis of the existing double-layer structure periosteum. Even if the periosteal material is degraded in the later stage, the inner layer and the outer layer of the undegraded part will still be tightly connected, and it can still resist the invasion of soft tissue and blood vessels in the later stage, provide sufficient mechanical support for the later repair of bone tissue and maintain structural stability, thereby improving the patient's rehabilitation effect.

[0009] According to one aspect of the present application, a PVA periosteal material for bone tissue regeneration is provided, which comprises an inner layer and an outer layer, wherein glutaraldehyde is coated between the inner layer and the outer layer;

[0010] The inner layer is in contact with the human bone repair material, and the inner layer is a nanofiber layer formed by using 2-hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol as a matrix and bioceramic particles as an additive;

[0011] The outer layer is a nanofiber layer formed by polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate.

[0012] The present application adopts 2-hydroxypropyl trimethyl ammonium chloride chitosan to replace traditional chitosan and polyvinyl alcohol as the matrix material of the inner layer, which can form a double cross-linked network in the matrix material, improve the bonding force between the two cross-linked networks, thereby improving the mechanical strength and degradability of the inner layer itself. In addition, the quaternary ammonium salt group contained in 2-hydroxypropyl trimethyl ammonium chloride chitosan can give the inner layer excellent antibacterial properties, and good antibacterial properties can be achieved without the need to add antibacterial agents or antibacterial particles. Compared with the method of adding antibacterial agents and antibacterial particles, this method can improve the uniformity of the distribution of antibacterial groups, thereby achieving uniform antibacterial properties and avoiding bone infection; the second is to reduce the presence of additional interfering substances, reduce human allergic reactions and affect the performance of periosteum. Bioceramic particles are also added to the inner layer, which can further enhance the mechanical strength of the inner layer, improve the mechanical compatibility with the outer layer, and ensure that the periosteum material still has good support and protection capabilities after late degradation.

[0013] The polyethyleneimine and chitosan oligosaccharide added in the outer layer, first, can improve the strength and mechanical uniformity of the outer layer, second, polyethyleneimine can produce hydrogen bonds with the inner layer matrix to form physical crosslinking, and chitosan oligosaccharide can form chemical crosslinking with the chitosan in the inner layer under the action of glutaraldehyde, thereby improving the bonding force between the inner layer and the outer layer, due to the presence of the above two crosslinkings, even if the periosteal material is degraded, the inner layer and the outer layer will not be stratified, ensuring that it plays a role normally. In addition, since the inner layer and the outer layer are double crosslinked by chemical crosslinking and physical crosslinking, in the degradation of the periosteal material, even if part of the chemical crosslinking does not exist, part of the physical crosslinking breaks, due to the presence of the above substances, a new hydrogen bond crosslinking structure will also be formed, thereby ensuring the crosslinking of the inner layer and the outer layer during the degradation process, until the final periosteal material is all absorbed. The molecular weight of chitosan oligosaccharide is lower than that of inner layer chitosan, and the biocompatibility of the periosteal material can be improved, and the absorption of the periosteal material by the human body is promoted.

[0014] Optionally, the weight ratio of 2-hydroxypropyltrimethylammonium chloride chitosan to polyvinyl alcohol in the inner layer is 1:(2.5-2.8);

[0015] The weight ratio of polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate in the outer layer is 1: (1-1.5): (2.0-3.0): (0.003-0.005).

[0016] The above dosage can improve the mechanical properties of the inner layer and the outer layer themselves, and can also control the degradation rate of the periosteum material, making the degradation rate moderate, which is more conducive to promoting the formation of new bone.

[0017] Optionally, the thickness of the inner layer is 4-5 mm, and the thickness of the outer layer is 0.15-0.25 mm.

[0018] Optionally, the bioceramic particles are 1.5 to 2.0 times the weight of the 2-hydroxypropyltrimethylammonium chloride chitosan.

[0019] The added bioceramic particles can strengthen the inner fiber membrane and provide raw materials for the regeneration of new bone, accelerate bone regeneration, improve recovery efficiency, and shorten treatment time. The amount of the above-mentioned bioceramic particles can maximize the strength of the inner layer and the overall periosteal material.

[0020] Optionally, the bioceramic particles are composed of hydroxyapatite and β-tricalcium phosphate in a weight ratio of 1:2. The hydroxyapatite and β-tricalcium phosphate are both in the nanometer range, preferably with a particle size of less than 50 nm.

[0021] The bioceramic particles of the above two substances can promote each other's dispersion in the inner layer, avoid agglomeration, and improve the mechanical uniformity of the periosteal material.

[0022] Optionally, the hydroxyapatite is prepared by modification with 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide:

[0023] The hydroxyapatite is placed in a modification liquid containing 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide, treated at 70-80° C. for 5-6 hours, filtered and washed to obtain the modified liquid.

[0024] The use of 3-mercaptopropyltriethoxysilane to modify hydroxyapatite can form a hydrogen bond connection between hydroxyapatite and the polyvinyl alcohol matrix. This hydrogen bond connection not only exists in the early stage of periosteum application, but also exists in the later stage of periosteum degradation. Trimethylsilylethylene oxide can cross-link with the amino groups in 2-hydroxypropyltrimethylammonium chloride chitosan or the amino groups in chitosan oligosaccharides, thereby achieving chemical cross-linking between hydroxyapatite and the inner and outer layers. Therefore, the above-mentioned modification method of hydroxyapatite is set according to the material properties in the current inner and outer layers. Through the above-mentioned cross-linking, the dispersibility of hydroxyapatite in the periosteum material and the bonding with the inner and outer layers can be achieved, thereby improving the mechanical uniformity of the periosteum material after late degradation, thereby providing a solid guarantee for the repair of bone tissue in the later stage.

[0025] The hydroxyapatite modified by the above substances can further promote the dispersion effect on β-tricalcium phosphate, so that both bioceramic particles can be evenly dispersed in the periosteum material.

[0026] Optionally, the weight ratio of the hydroxyapatite, 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide is 1:(0.2-0.3):(0.2-0.3).

[0027] This dosage can ensure that the above-mentioned effects are exerted while reducing interference and enhancing the effect of hydroxyapatite in promoting bone cell proliferation and differentiation.

[0028] According to another aspect of the present application, a method for preparing the PVA periosteal material for bone tissue regeneration described in any one of the above items is provided, comprising the following steps:

[0029] (1) adding the 2-hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol to a first solvent to prepare a solution with a concentration of 10-15%, heating to 80-85° C. and stirring for at least 10 hours, then cooling, adding bioceramic particles to obtain an inner electrospinning solution, and then electrospinning to obtain an inner nanofiber membrane;

[0030] (2) cross-linking the inner nanofiber membrane with glutaraldehyde, cutting the cross-linked nanofiber membrane into pieces after drying, adding a mixed solvent of tert-butyl alcohol and water, stirring to obtain a fiber dispersion, transferring the fiber dispersion into a preparation container after homogenization and stirring, controlling the thickness to be 4-5 mm, freezing at -30~-20°C, and then vacuum drying at -10~0°C to obtain the inner layer;

[0031] (3) Add the polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate to the second solvent, stir evenly to obtain an outer layer electrospinning solution with a concentration of 25-30%, prepare the inner layer coating glutaraldehyde solution in step (2), electrospin the outer layer electrospinning solution onto the inner layer coated with glutaraldehyde to form an outer layer, and let it stand at 25-30°C for at least 2 hours.

[0032] In the preparation method, the inner layer prepared by steps (1) and (2) is a fiber membrane with micropores, which is conducive to the growth and climbing of osteoblasts. The outer layer is directly electrospun on the inner layer coated with glutaraldehyde. At this time, the inner layer and the outer layer have been bonded. By standing at 25-30°C, physical crosslinking and chemical crosslinking can be formed between the inner layer and the outer layer, thereby improving the periosteum material with tight bonding between the inner layer and the outer layer.

[0033] Optionally, the amount of glutaraldehyde added in step (2) is 10%-15% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan, and the amount of glutaraldehyde solution coated on the inner layer is 5-10% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan.

[0034] The amount of glutaraldehyde added in step (2) is to achieve self-crosslinking of the 2-hydroxypropyltrimethylammonium chloride chitosan in the inner layer. However, there are still a large number of amino groups in the crosslinked network in order to facilitate the subsequent crosslinking with the outer layer through the coated glutaraldehyde. The glutaraldehyde coated on the inner layer can achieve chemical crosslinking between the inner layer and the outer layer, thereby maximizing the number of crosslinking points between the inner layer and the outer layer.

[0035] Optionally, in the mixed solvent of tert-butanol and water in step (2), the volume ratio of tert-butanol to water is 20:80, and the weight ratio of the nanofiber membrane to the mixed solvent is 1:200.

[0036] Optionally, the homogenization stirring time in step (2) is 2-3 hours.

[0037] The electrospinning parameters of steps (1) and (3) may adopt the parameters commonly used in the prior art, and the specific parameters do not constitute a limitation to the present application.

[0038] According to another aspect of the present application, provided is the use of the PVA periosteal material for bone tissue regeneration described in any one of the above or the PVA periosteal material for bone tissue regeneration prepared by the preparation method of the PVA periosteal material for bone tissue regeneration described in any one of the above in bone tissue regeneration and repair.

[0039] The beneficial effects of this application include but are not limited to:

[0040] 1. The PVA periosteum material for bone tissue regeneration of the present application can achieve chemical and physical crosslinking between the inner and outer layers by adding polyethyleneimine and chitosan oligosaccharide to the outer layer and glutaraldehyde between the outer and inner layers, thereby improving the bonding strength between the inner and outer layers and ensuring that the undegraded part can still play a good role during the later degradation.

[0041] 2. The PVA periosteal material for bone tissue regeneration of the present application has a porous nanofiber membrane as the inner layer, which provides a good environment and space for the proliferation and differentiation of osteoblasts, can promote the growth of osteoblasts, and the degradation rate matches the growth rate of new bone, thereby improving the recovery effect of patients.

[0042] 3. The PVA periosteal material for bone tissue regeneration of the present application uses 2-hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol as a matrix in the inner layer, which can not only improve the biological and mechanical similarity with the natural periosteum, but also give the periosteum material excellent antibacterial properties and improve the biocompatibility of the periosteum material.

[0043] 4. The material used in the outer layer of the PVA periosteal material for bone tissue regeneration of the present application can improve the mechanical properties of the periosteal material, play a good supporting role and block the growth of other soft tissues, which is beneficial to the regeneration and repair of bone tissue.

[0044] 5. The PVA periosteal material for bone tissue regeneration of the present application has a low swelling rate and good degradation performance, good biocompatibility, simple preparation steps, mild chemical and physical cross-linking conditions for the inner and outer layers, and does not affect the properties of the inner and outer layers themselves. DETAILED DESCRIPTION

[0045] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0046] Unless otherwise specified, the raw materials in the examples and comparative examples of this application were purchased through commercial channels. 2-Hydroxypropyltrimethylammonium chloride chitosan was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., polyvinyl alcohol (CAS: 9002-89-5), hydroxyapatite (CAS: 130-66-5), and β-tricalcium phosphate (CAS: 7758-87-4) were purchased from Shanghai Yuanye Biotechnology Co., Ltd., and the particle sizes of hydroxyapatite and β-tricalcium phosphate were all below 50 nm, 3-mercaptopropyltriethoxysilane (CAS: 14814-09-6) was purchased from Hubei Fangde New Materials Co., Ltd., and trimethylsilylepoxy Ethane (CAS: 16722-09-1) was purchased from Shanghai Quanxin Import and Export Trading Co., Ltd., polydioxanone (CAS: 31621-87-1), polyethyleneimine (CAS: 9002-98-6), chitosan oligosaccharide (CAS: 148411-57-8), chitosan (CAS: 9012-76-4) and sodium dodecyl sulfate (CAS: 151-21-3) were purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd., and acetic acid, tert-butyl alcohol, dimethylformamide, glutaraldehyde and dichloromethane were all purchased from Aladdin.

[0047] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.

[0048] Example 1

[0049] This embodiment relates to a PVA periosteal material for bone tissue regeneration and a preparation method thereof, the preparation method comprising the following steps:

[0050] (1) 2-Hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol in a weight ratio of 1:2.5 were added to acetic acid to prepare a solution with a concentration of 10%, heated to 85°C and stirred for 10 hours, then cooled, and bioceramic particles were added to obtain an inner electrospinning solution, and then electrospinning was performed to obtain an inner nanofiber membrane. The bioceramic particles were 2.0 times the weight of 2-Hydroxypropyltrimethylammonium chloride chitosan, and the bioceramic particles were composed of hydroxyapatite and β-tricalcium phosphate in a weight ratio of 1:2;

[0051] (2) The inner layer of the nanofiber membrane was cross-linked with glutaraldehyde, the amount of glutaraldehyde added was 10% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan, and the cross-linked nanofiber membrane was cut into pieces after drying at 50°C for 30 min. A mixed solvent of tert-butyl alcohol and water was then added and stirred to obtain a fiber dispersion. The volume ratio of tert-butyl alcohol to water was 20:80, and the weight ratio of the nanofiber membrane to the mixed solvent was 1:200. After homogenization and stirring for 2 h, the fiber dispersion was transferred to a preparation container with a controlled thickness of 4 mm. After low-temperature freezing at -30~-20°C, it was placed in a vacuum dryer at -10~0°C to obtain an inner layer with a thickness of 4 mm.

[0052] (3) Add polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate in a weight ratio of 1:1:3.0:0.003 to dimethylformamide, stir evenly to obtain an outer electrospinning solution with a concentration of 25%, and coat the inner layer prepared in step (2) with a glutaraldehyde solution accounting for 10% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan. Electrospin the outer electrospinning solution onto the inner layer coated with glutaraldehyde to form an outer layer with a thickness of 0.15 mm, and let it stand at 30°C for 2 h.

[0053] Example 2

[0054] This embodiment relates to a PVA periosteal material for bone tissue regeneration and a preparation method thereof, the preparation method comprising the following steps:

[0055] (1) 2-Hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol in a weight ratio of 1:2.8 were added to acetic acid to prepare a solution with a concentration of 15%, heated to 80°C and stirred for 12 hours, then cooled, and bioceramic particles were added to obtain an inner electrospinning solution, and then electrospinning was performed to obtain an inner nanofiber membrane. The bioceramic particles were 1.5 times the weight of 2-Hydroxypropyltrimethylammonium chloride chitosan, and the bioceramic particles were composed of hydroxyapatite and β-tricalcium phosphate in a weight ratio of 1:2;

[0056] (2) The inner layer of the nanofiber membrane was cross-linked with glutaraldehyde, the amount of glutaraldehyde added was 15% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan, and the cross-linked nanofiber membrane was cut into pieces after drying at 50°C for 30 min. A mixed solvent of tert-butyl alcohol and water was then added and stirred to obtain a fiber dispersion. The volume ratio of tert-butyl alcohol to water was 20:80, and the weight ratio of the nanofiber membrane to the mixed solvent was 1:200. After homogenization and stirring for 3 h, the fiber dispersion was transferred to a preparation container with a controlled thickness of 5 mm. After low-temperature freezing at -30~-20°C, it was placed in a vacuum dryer at -10~0°C to obtain an inner layer with a thickness of 5 mm.

[0057] (3) Add polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate in a weight ratio of 1:1.5:2.0:0.005 to dimethylformamide, stir evenly to obtain an outer electrospinning solution with a concentration of 30%, and coat the inner layer prepared in step (2) with a glutaraldehyde solution accounting for 5% by weight of 2-hydroxypropyltrimethylammonium chloride chitosan. Electrospin the outer electrospinning solution onto the inner layer coated with glutaraldehyde to form an outer layer with a thickness of 0.25 mm, and let it stand at 25°C for 4 hours.

[0058] Example 3

[0059] This embodiment relates to a PVA periosteal material for bone tissue regeneration and a preparation method thereof, the preparation method comprising the following steps:

[0060] (1) 2-Hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol in a weight ratio of 1:2.6 were added to acetic acid to prepare a solution with a concentration of 10%, heated to 85°C and stirred for 13 hours, then cooled, and bioceramic particles were added to obtain an inner electrospinning solution, and then electrospinning was performed to obtain an inner nanofiber membrane. The bioceramic particles were 2.0 times the weight of 2-Hydroxypropyltrimethylammonium chloride chitosan, and the bioceramic particles were composed of hydroxyapatite and β-tricalcium phosphate in a weight ratio of 1:2;

[0061] (2) The inner layer of the nanofiber membrane was cross-linked with glutaraldehyde, the amount of glutaraldehyde added was 15% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan, and the cross-linked nanofiber membrane was cut into pieces after drying at 50°C for 30 min. A mixed solvent of tert-butyl alcohol and water was then added and stirred to obtain a fiber dispersion. The volume ratio of tert-butyl alcohol to water was 20:80, and the weight ratio of the nanofiber membrane to the mixed solvent was 1:200. After homogenization and stirring for 3 h, the fiber dispersion was transferred to a preparation container with a controlled thickness of 4.5 mm. After low-temperature freezing at -30~-20°C, it was placed in a vacuum dryer at -10~0°C to obtain an inner layer with a thickness of 4.5 mm.

[0062] (3) Add polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate in a weight ratio of 1:1.2:2.5:0.004 to dimethylformamide, stir evenly to obtain an outer electrospinning solution with a concentration of 30%, and coat the inner layer with a glutaraldehyde solution accounting for 8% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan prepared in step (2). Electrospin the outer electrospinning solution onto the inner layer coated with glutaraldehyde to form an outer layer with a thickness of 0.2 mm, and let it stand at 30°C for 3 hours.

[0063] Example 4

[0064] The difference between this embodiment and embodiment 3 is that zinc oxide is used to replace hydroxyapatite, and the rest is the same as embodiment 3.

[0065] Example 5

[0066] The difference between this embodiment and embodiment 3 is that the bioceramic particles are 3.0 times the weight of 2-hydroxypropyltrimethylammonium chloride chitosan, and the rest is the same as embodiment 3.

[0067] Example 6

[0068] The difference between this embodiment and embodiment 3 is that the weight ratio of hydroxyapatite to β-tricalcium phosphate is 2:1, and the rest is the same as embodiment 3.

[0069] Example 7

[0070] The difference between this embodiment and embodiment 3 is that hydroxyapatite is prepared by modification with 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide:

[0071] Hydroxyapatite is placed in a dichloromethane solution containing 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide, the weight ratio of hydroxyapatite, 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide is 1:0.2:0.3, and treated at 70°C for 6h. The mixture is filtered and washed to obtain a product. The rest is the same as Example 3.

[0072] Example 8

[0073] The difference between this embodiment and embodiment 3 is that hydroxyapatite is prepared by modification with 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide:

[0074] Hydroxyapatite is placed in a dichloromethane solution containing 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide, the weight ratio of hydroxyapatite, 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide is 1:0.3:0.2, and treated at 80°C for 5h. The mixture is filtered and washed to obtain a product. The rest is the same as Example 3.

[0075] Example 9

[0076] The difference between this embodiment and embodiment 7 is that trimethylsilylethylene oxide is not used for modification, and only 3-mercaptopropyltriethoxysilane is used to modify the hydroxyapatite. The rest is the same as embodiment 7.

[0077] Example 10

[0078] The difference between this embodiment and embodiment 7 is that 3-mercaptopropyltriethoxysilane is not used for modification, and only trimethylsilylethylene oxide is used to modify the hydroxyapatite. The rest is the same as embodiment 7.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 3 is that chitosan is used in the inner layer instead of 2-hydroxypropyltrimethylammonium chloride chitosan, and the rest is the same as Example 3.

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 3 is that polyethyleneimine is not added to the outer layer, and the rest is the same as Example 3.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 3 is that chitosan oligosaccharide is not added to the outer layer, and the rest is the same as Example 3.

[0085] Comparative Example 4

[0086] The difference between this comparative example and Example 3 is that glutaraldehyde is not coated between the inner layer and the outer layer, and the rest is the same as Example 3.

[0087] Test Example 1 Mechanical Properties

[0088] The mechanical properties of the periosteal materials prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 1, where the Young's modulus was measured using GB / T 37788-2019, and the elongation at break and tensile strength were measured using GB / T10654-2001.

[0089] Table 1

[0090]

[0091] In order to verify the change of mechanical strength of periosteum material after degradation for a certain period of time, the tensile strength decrease rate of the periosteum material after degradation for 14 days in the physiological conditions of in vitro artificial degradation fluid with a pH value of 7.4 was tested, as well as whether the appearance of the periosteum was stratified. The results are shown in Table 2. Decline rate = (initial tensile strength value - tensile strength value after degradation) / initial tensile strength value × 100%.

[0092] Table 2

[0093]

[0094] According to 2, the mechanical properties of the periosteal material of the present application will also decrease as degradation proceeds, which is consistent with the basic characteristics of the periosteal material. According to the comparison between comparative examples 2-4 and embodiment 3, when the cross-linking points between the inner layer and the outer layer are reduced, individual regions will delaminate after a certain period of degradation, so the mechanical strength and degradation rate will decrease faster.

[0095] Test Example 2 Water Swelling and Degradability

[0096] The periosteum materials prepared in the above embodiments and comparative examples were tested for water absorption, swelling and degradability. The results are shown in Table 3. The specific test methods are as follows:

[0097] Water absorption and swelling: The initial mass of the periosteal material was measured as W0. Each periosteal material was immersed in PBS buffer with a pH of 7.4 and placed at a constant temperature of 37°C. The material was taken out every hour and the surface moisture was absorbed with filter paper and then weighed until the final weight remained unchanged, which was recorded as W1. The water absorption and swelling rate was calculated using the following formula: [(W1-W0) / W0]×100%.

[0098] Degradability: The initial mass W0 of the periosteal material was measured, and each periosteal material was immersed in an artificial degradation solution with a pH value of 7.4 and degraded at 37°C for 14 days and 28 days. The weight W14 at 14 days and the weight W28 at 28 days were recorded, and the degradation rate was calculated. The degradation rate = [(weight before degradation - weight after degradation) / weight before degradation] × 100%.

[0099] Table 3

[0100]

[0101] According to the data in Table 3 above, the water absorption and swelling rate of the periosteal material prepared in the present application is between 126% and 135%, which proves that its volume does not change much after implantation into the human body and can be well fixed in the original position to promote bone repair.

[0102] The degradation rate of the periosteal material of the present application is moderate, which can ensure that the periosteal material gradually degrades as new bone is gradually generated over time and does not cause a burden on the human body.

[0103] According to the comparison between Comparative Example 1 and Example 3, the degradation rate of the periosteal material using chitosan decreases. The possible reason is that the cross-linking points formed by chitosan itself in the inner layer increase, and the cross-linking points between the chitosan and the outer layer increase, so the water absorption swelling rate and degradation rate are lower than those in Example 3.

[0104] According to the comparison between Comparative Examples 2-4 and Example 3, reducing the cross-linking points between the inner layer and the outer layer or avoiding cross-linking can increase the water absorption, swelling rate and degradation rate of the periosteal material. However, the degradation rate is not the higher the better, but needs to be best adapted to the growth rate of the new bone. Therefore, the periosteal material of the present application can be adjusted according to the patient's age and bone age to obtain a periosteal material that is suitable for the patient's recovery.

[0105] According to the comparison between Example 4 and Example 3, it can be seen that, when the inner and outer matrixes of the present application remain unchanged, the addition of zinc oxide will increase the degradation rate of the periosteal material. According to the comparison between Examples 5-6 and Example 3, it can be seen that the amount of ceramic material added and the ratio of specific substances will also affect the degradation rate to a certain extent.

[0106] Test Example 3 Osteogenesis Induction

[0107] The periosteum materials of Example 3, Example 7 and Comparative Examples 1-4 were tested for ALP activity, and the specific test was as follows:

[0108] The expression of ALP in cells was detected by alkaline phosphatase kit. The whole process was carried out on ice. First, the total protein in the cells was extracted, the culture medium in the well was discarded, and the periosteum materials seeded with human bone marrow mesenchymal stem cells for 14 days were washed 3 times with pre-cooled PBS. RIPA cell lysis buffer containing 250μL 1mMPMSF was added to the wells and lysed on ice for 15 min. After the cells were lysed, the mixed solution was aspirated into a 1.5 mL EP tube, centrifuged at 12000 rpm for 10 min at 4°C, and the supernatant was aspirated for use. Then the protein concentration was determined using the BCA protein concentration kit. The protein concentration standard curve was first constructed using standard protein. The concentrations of the standard curve were: 0 g / mL, 0.5 g / mL, 1 mL, 2.5 mL, 5 mL, 10 mL, 20 mL and 40 mL. Add 150 μL of working solution to the 96-well plate, then add 150 μL of standard sample and sample to be tested, mix for a few minutes, react at 37°C for 2 hours, cool to room temperature after the reaction, and use a microplate reader for detection. Finally, use the alkaline phosphatase kit to detect the ALP content. First, mix the kit buffer matrix liquid into the working solution according to the instructions, then add 4 μL of the sample to be tested to the 96-well plate, then add 200 μL of working solution, react at 37°C for 15 minutes, and finally place it in a microplate reader for detection.

[0109] The ALP activity was determined by the ratio of ALP content to protein content. The test results are shown in Table 4.

[0110] Table 4

[0111]

[0112] According to the data in the above table, the periosteum material prepared in the present application has a good effect of inducing osteogenic differentiation, thereby promoting the repair of bone tissue.

[0113] Test Example 4 Antibacterial Properties

[0114] The colony counting method was used to determine the Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli as experimental objects. The test results are shown in Table 5. Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli were cultured in a shaker for 18 h (37°C and 100 rpm), and then the bacterial solution was diluted with sterile PBS to obtain 1.0×10 5 CFU / mL concentration of bacterial suspension. The sterilized hydrogel extract was placed in a 24-well plate, and 20 μL of the diluted bacterial suspension was added to each well of the hydrogel extract. The wells without samples were used as controls and incubated in an incubator at 37°C. After 2 hours, the well plate was taken out, 1 mL of culture medium was added to each well, and it was gently shaken. Then 20 μL of bacterial suspension was applied to the solid agar plate, and the colony growth was observed after 24 hours of culture, and the colonies were technically tested. The calculation formula is: Inhibition rate (%) = 1-Q / W × 100%, W is the number of Gram-positive Staphylococcus aureus or Gram-negative Escherichia coli in the control group, and Q is the number of Gram-positive Staphylococcus aureus or Gram-negative Escherichia coli in the sample group.

[0115] Table 5

[0116]

[0117] According to the data in the above table, the periosteal material prepared in the present application can have good antibacterial properties without adding additional antibacterial agents, and the antibacterial effect of zinc oxide ceramic particles added in Example 4 is the best, because the zinc oxide particles and 2-hydroxypropyltrimethylammonium chloride chitosan quaternary ammonium salt promote each other and jointly improve the antibacterial effect. According to the comparison between Comparative Example 1 and Example 3, when chitosan without quaternary ammonium salt groups is used, the antibacterial rate is significantly reduced, and it is difficult to use normally without adding additional antibacterial agents.

[0118] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A PVA periosteal material for bone tissue regeneration, characterized in that: It comprises an inner layer and an outer layer, wherein glutaraldehyde is coated between the inner layer and the outer layer; The inner layer is in contact with the human bone repair material. The inner layer is a nanofiber layer formed by using 2-hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol as a matrix and bioceramic particles as an additive. The weight ratio of 2-hydroxypropyltrimethylammonium chloride chitosan to polyvinyl alcohol in the inner layer is 1: (2.5-2.8); The outer layer is a nanofiber layer formed by polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium lauryl sulfate, and the weight ratio of polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium lauryl sulfate in the outer layer is 1: (1-1.5): (2.0-3.0): (0.003-0.005); The bioceramic particles are composed of hydroxyapatite and β-tricalcium phosphate in a weight ratio of 1:2, the hydroxyapatite is prepared by modification with 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide, the weight of the bioceramic particles is 1.5-2.0 times that of the 2-hydroxypropyltrimethylammonium chloride chitosan, and the weight ratio of the hydroxyapatite, 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide is 1: (0.2-0.3): (0.2-0.3): The hydroxyapatite is placed in a modification liquid containing 3-mercaptopropyltriethoxysilane and trimethylsilylethylene oxide, treated at 70-80° C. for 5-6 hours, filtered and washed to obtain the modified liquid.

2. The PVA periosteal material for bone tissue regeneration according to claim 1, characterized in that: The thickness of the inner layer is 4-5 mm, and the thickness of the outer layer is 0.15-0.25 mm.

3. The method for preparing the PVA periosteal material for bone tissue regeneration according to any one of claims 1 to 2, characterized in that: The steps include: (1) adding the 2-hydroxypropyltrimethylammonium chloride chitosan and polyvinyl alcohol to a first solvent to prepare a solution with a concentration of 10-15%, heating to 80-85° C. and stirring for at least 10 hours, then cooling, adding bioceramic particles to obtain an inner electrospinning solution, and then electrospinning to obtain an inner nanofiber membrane; (2) cross-linking the inner nanofiber membrane with glutaraldehyde, cutting the cross-linked nanofiber membrane into pieces after drying, adding a mixed solvent of tert-butyl alcohol and water, stirring to obtain a fiber dispersion, transferring the fiber dispersion into a preparation container after homogenization and stirring, controlling the thickness to be 4-5 mm, freezing at -30~-20°C, and then vacuum drying at -10~0°C to obtain the inner layer; (3) Add the polydioxanone, polyethyleneimine, chitosan oligosaccharide and sodium dodecyl sulfate to the second solvent, stir evenly to obtain an outer electrospinning solution with a concentration of 25-30%, coat the inner layer prepared in step (2) with glutaraldehyde solution, electrospin the outer electrospinning solution onto the inner layer coated with glutaraldehyde to form an outer layer, and let stand at 25-30°C for at least 2 hours.

4. The method for preparing the PVA periosteal material for bone tissue regeneration according to claim 3, wherein: In step (2), the amount of glutaraldehyde added is 10%-15% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan, and the amount of glutaraldehyde solution coated on the inner layer is 5-10% of the weight of 2-hydroxypropyltrimethylammonium chloride chitosan.

5. Use of the PVA periosteal material for bone tissue regeneration as described in any one of claims 1-2 or the PVA periosteal material for bone tissue regeneration prepared by the preparation method of the PVA periosteal material for bone tissue regeneration as described in any one of claims 3-4 in bone tissue regeneration and repair.